It ends with us / Colleen Hoover. - Hoover, Colleen (Simon & Schuster, 2016)
Lily has come a long way from the small town in Maine where she grew up. She graduated from college, moved to Boston, and started her own business. So when she feels a spark with a gorgeous neurosurgeon named Ryle Kincaid everything in Lily's life suddenly seems almost too good to be true. Ryle is assertive, stubborn, and maybe even a little arrogant. He's also sensitive, brilliant and has a total soft spot for Lily. Lily can't get him out of her head, but Ryle's complete aversion to relationships is disturbing. Even as Lily finds herself becoming the exception to his no dating rule, she can't help but wonder what made him that way in the first place. As questions about her new relationship overwhelm her, so do thoughts of Atlas Corrigan, her first love and a link to the past she left behind. When Atlas suddenly reappears everything Lily has built with Ryle is threatened.
Originally published: New York: Atria Paperbacks.
Keywords: Love stories.